2021
DOI: 10.3892/etm.2021.10904
|View full text |Cite
|
Sign up to set email alerts
|

miR‑199b‑5p mediates adriamycin‑induced podocyte apoptosis by inhibiting the expression of RGS10

Abstract: Podocyte apoptosis is a key risk factor for the progression of kidney diseases. MicroRNA (miR)-199b-5p has been shown to be involved in cell apoptosis. However, the molecular mechanisms of miR-199b-5p in podocyte apoptosis remain uncertain. Thus, the present study aimed to investigate whether miR-199b-5p participates in the regulation of podocyte apoptosis and to elucidate the involved mechanisms of this process. A podocyte apoptosis model was constructed using adriamycin (ADR) in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Podocyte apoptosis is caused by many factors, including drugs, infection, and immune disorders[ 55 - 57 ]. ADR is one of the drugs that causes podocyte apoptosis due to its pharmacological action and distribution[ 58 ]. However, how to protect podocytes from ADR needs further research to find more effective targeted drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Podocyte apoptosis is caused by many factors, including drugs, infection, and immune disorders[ 55 - 57 ]. ADR is one of the drugs that causes podocyte apoptosis due to its pharmacological action and distribution[ 58 ]. However, how to protect podocytes from ADR needs further research to find more effective targeted drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNAs (including mRNA and microRNA) was purified from kidney and mTECs using TRIzol® reagent (Life Technologies; Agilent, Inc., USA). RT‐qPCR was performed and analysed as described previously 19 . The primers sequences are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…RT‐qPCR was performed and analysed as described previously. 19 The primers sequences are shown in Table 1 . The thermocycling conditions were presented in Tables 2 and 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Lin et al (2018) recently described Enterococcus faecalis as a causative agent of persistent apical periodontitis with the ability to augment autophagy by suppressing the PI3K/Akt/mTOR signalling pathway in macrophages; this may lead to persistent inflammation in the periapical region, highlighting the relationship between autophagy and apical periodontitis. It has been reported that overexpression of RGS10 in kidney diseases can inhibit the mTOR signalling pathway, which is a known negative regulator of TFEB (Napolitano et al, 2018; Qu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%